THE IMPACT OF TOURISM IN THE MOUNTAIN VILLAGE OF GRINDELWALD: AN ANALYSIS OF THE ECONOMIC, SOCIAL, AND ECOLOGICAL INFLUENCES - dally, lea marie; wijayanti, ra afera ratna (IULI Publisher, 2025)
This research investigates the impact of tourism on the mountain village of Grindelwald. The primary goal is to analyse the impact according to the economical, social and eco- logical influences. Through expert interviews the research provides a comprehensive overview of the impacts of tourism in Grindelwald and its current situation as well as its challenges and its future perspectives. Recommendations for action are offered to con- tribute to the development of a sustainable future. This study aims to contribute insights of the impact’s tourism can have in a rural area, specifically Grindelwald. Keywords: Tourism, Rural Tourism, Overtourism, Sustainability, Grindelwald, Economic, Social, Ecologic